Ketahanan Terimbas Tanaman Kacang-kacangan terhadap Penyakit - Alfi Inayati (Puslitbang Tanaman Pangan, 2016)
Legumes have an important role especially as a source of nutrition, important in maintaining soil quality, and as animal feed. Although the production and the needs for legumes continues to rise, the productivity especially at the farm level is still low. This is mainly due to pests and diseases infections and also the soil infertility effects. Yield losses due to pests and diseases is quite high up to 80%. Induced resistance is one effort to control the disease and improve the growth quality of legumes. Various elicitors (biotic and abiotic) and induced mechanisms have been tested and reported to give promising results. Induced resistance was reported to increase the resistance of leguminous plants against pathogen infection such as fungi, bacteria, and viruses that are transmitted through soil, seed-borne, and from the surface of the leaves, such as: Sclerotium rolfsii, Rhizoctonia solani, Fusarium sp, Aspergillus flavus, Cercosporidium personatum, Xanthomonas axonopodis, peanut mottle virus, and soybeant stunt virus. Recently, the use of induced resistance in Indonesia is very limited. The use of Trichoderma sp, non-pathogenic Fusarium, and Pseudomonas fluoroscent as biocontrol agents has been started although in a limited numbers. In the future, induced resistance will become one component that is important in controlling the disease in an integrated pest management.